Traumatic Perforation – Etiology, Outcome and Factors Affecting the Outcome - Roshan Acharya,; Bishow Tulachan,; Anup Acharya,; Anuj Devkota, (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Traumatic tympanic membrane perforation is the most common type of trauma – induced otologic dysfunction. The study is aimed to evaluate factors affecting healing of truamatic tympanic membrane perforation after 12 weeks. MATERIAL AND METHODS A prospective observational study conducted at UCMS, Bhairahawa, Nepal. Sixty patients with traumatic tympanic membrane perforation were evaluated on the basis of causes of trauma, symptoms, otoscopic examination, size of perforation and other factors affecting the outcome of perforation. Healing status of tympanic membrane was assessed 12-week post injury. RESULTS The age of the patients ranged from 4-79 years with mean age (years) of 27.84 ± 13.16. Otalgia was seen in 36 (60%) followed by hearing loss 21 (35%) and least common was vertigo 2 (3%). Most common etiology for injury was ‘Slap’(30%) followed by fall injury and physical assault excluding slap with each comprising 16%. Number of patients with small, medium and large perforations were 27 (45%), 21 (35%) and 12 (20%) respectively. After 12 weeks, 46 (77%) cases had healed perforation with best healing seen in younger patients having age group 11-40 years (26.28±13.5) and least in age group >60 years (52±25.11 ) with p value of 0.01. 97% cases of smaller perforation had healed tympanic membrane whereas in larger perforation healing was observed in only 42 % cases. CONCLUSION Age, size of perforation, types of traumas have signiﬁcant effect on outcomes of spontaneous healing. With cautious care and strong aural precautions, the prognosis of tympanic membrane perforation spontaneous healing is favourable.